Fluvial biotopes influence macroinvertebrate biodiversity in South‐East Asian tropical streams. Issue 12 (21st December 2016) - Baker, Kate; Chadwick, Michael A.; Kahar, Rafhiah; Sulaiman, Zohrah Haji; Wahab, Rodzay A.
Abstract: Given the widespread degradation of aquatic systems caused by land‐use changes associated with palm oil production in South‐East Asia, it is imperative to identify and study the remaining undisturbed rivers and streams. Stream macroinvertebrates are reliable indicators of environmental health. Linking the community structure of these organisms to natural hydraulic and geomorphic conditions (categorized as biotopes) is vital for the conservation and restoration of streams. This study characterizes the effects of biotopes on macroinvertebrate community structure in three streams within Ulu Temburong National Park in northern Borneo. Biotopes within these streams were categorized as either bedrock (waterfalls and cascades) or mixed substrate (riffles and pools). In total, 119 taxa were collected from all sampled biotopes, but not all taxa were collected from each stream. Biotopes were statistically distinct in terms of taxonomic richness, but not mean individual density or average community biomass. There were differences in community structure between waterfalls, cascades, pools, and riffles. The survey suggests that pool and riffle biotopes were more vulnerable to scouring flows and had similar community structure, while waterfalls and cascades likely experienced lower sheer stress during floods and had similar macroinvertebrate communities. This study has found that classification and mapping of macroinvertebrates with biotope theory in pristine, tropical streams is a useful framework for simplifying the many linkages between ecology, geomorphology, and hydrology. These natural patterns increase our understanding of tropical streams and can be used to assess the impacts of forest degradation.